The Design of local placement detector for cable accessories based on ultrasonic technology. Issue 1 (1st February 2023) - Zhao, Tiemin; Liu, Jianshu; Zheng, Shiyang; Yang, Le; Ding, Zhen; Li, Dongsheng; Li, Kai; Li, Wenpeng; Yang, Xue; Chai, Fangsen
Abstract: In the process of cable transmission, the existence of air gap, tip, burr and other conditions will cause partial discharge phenomenon and lead to cable insulation aging, which can affect the safety of power transmission. Partial discharge detection can detect early insulation defects accurately, timely and efficiently. It is an ideal method to detect the occurrence of PD by ultrasonic wave which is the by-product of PD because it is less affected by electromagnetic interference. At the same time, a clamping device is designed, which is compact in structure, easy to carry and high in accuracy. This discharge detector can reduce the degree of external interference in the detection process, improve the accuracy of ultrasonic waveform, accurately identify whether partial discharge occurs, and alarm.